Accounting for equality: Gender budgeting and moderate feminism. Issue 8 (21st December 2018) - Marx, Ulrike
Abstract : This article sheds light on the relationship between quantification and calculative practices of accounting and moderate feminism. Drawing on a case of gender budgeting in Austria and the literature on social studies of accounting, I show how gender equality initiatives are translated into practice and come to codify the governance of gender relations through calculative practices that further the logic of neoliberal governmentality, rather than fundamentally challenging it. As such, this article provides an account of one site of the neoliberal recuperation of feminist critique through technologies of quantification and accountability.